PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS III SDN BABARSARI MENGGUNAKAN MODEL PROBLEM BASED LEARNING - ANASTASIA EKA SAN DIANA; RISHE PURNAMA DEWI; JAROT PRAKOSO (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
The background of this research is the activity and learning outcomes of third-grade students of SD Negeri Babarsari in the thematic learning of Indonesian language content, which is still low. Improvements are needed in order to increase the activity and learning outcomes of third-grade students of SD Negeri Babarsari. This study aimed to describe the increase in activity and learning outcomes of third-grade students at SD Negeri Babarsari using a Problem Based Learning model with the help of domino card media. This research is a Classroom Action Research (CAR). The subjects of this study were third-grade students of SD Negeri Babarsari with a total of 28 students. This CAR design consists of two cycles using the Kemmis and Targgart models which include planning, action, observation, and reflection. Data collection techniques using observation, documentation, and tests. The data analysis used is mix-method (descriptive and quantitative). The results showed an increase in the percentage of student activity. This can be seen from the results of student observations in the pre-cycle to cycle II, which is 38.68% in the pre-cycle, 75.30% in the first cycle, while in the second cycle it is 77.77%. This is accompanied by an increase in the average value of student learning outcomes from the pre-cycle of 63.57, increasing in the first cycle to 70.37 and in the second cycle increasing to 82.96. It can be concluded that the Problem Based Learning model using card media can increase the activity and learning outcomes of third-grade students of SD Negeri Bababrsari Yogyakarta. ABSTRAKLatar belakang penelitian ini mengenai keaktifan dan hasil belajar siswa kelas III SD Negeri Babarsari pada pembelajaran tematik muatan bahasa Indonesia yang masih rendah sehingga diperlukan perbaikan agar dapat meningkatkan keaktifan dan hasil belajar siswa kelas III SD Negeri Babarsari. Tujuan dari penelitian ini untuk mendeskripsikan peningkatan keaktifan dan hasil belajar siswa kelas III SD Negeri Babarsari menggunakan model Problem Based Learning berbantu media kartu domino. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Subjek penelitian ini adalah siswa kelas III SD Negeri Babarsari dengan jumlah 28 siswa. Desain PTK ini terdiri dari dua siklus dengan menggunakan model Kemmis dan Targgart yang meliputi perencanaan, tindakan, observasi, dan refleksi. Teknik pengumpulan data menggunakan observasi, dokumentasi dan tes. Analisis data yang digunakan adalah deskriptif kuantitatif. Hasil penelitian menunjukkan terdapat peningkatan persentase keaktifan siswa. Hal ini dapat dilihat dari hasil observasi siswa pada pra siklus hingga siklus II, yaitu pada pra siklus diperoleh sebesar 38,68%, pada siklus I sebesar 75,30%, sedangkan pada siklus II sebesar 77,77%. Hal tersebut diiringi dengan peningkatan nilai rata-rata hasil belajar siswa dari pra siklus sebesar 63,57 meningkat pada siklus I menjadi 70,37 dan pada siklus II meningkat menjadi 82,96. Dapat disimpulkan bahwa model Problem Based Learning menggunakan media kartu dapat meningkatkan keaktifan dan hasil belajar siswa kelas III SD Negeri Bababrsari Yogyakarta.